Redesign of The Mobile Banking User Interface at Bank XYZ Based on SystemLog Data and The Design Thinking Method - Bobi Kurniawan; Mahendrawathi ER (Journal of Social Research, 2026)
Launched in 2024, Bank XYZ's mobile banking application experienced an increase in active users, necessitating adjustments to its appearance to reflect user needs and trends. Although no negative feedback was found in the Play Store or App Store, analysis of system log data indicated features that were underutilized and transaction flows were inefficient. Furthermore, internal user feedback indicated that some menus were still not fully user-friendly. Research on mobile banking application interface redesign generally focuses on qualitative approaches based on observation and interviews, which are limited by their subjective nature and do not fully represent actual user behavior. Therefore, this study examines the redesign of Bank XYZ's mobile banking user interface by incorporating system log data analysis. This research aims to identify barriers and formulate solutions for improving the mobile banking application to increase usability and optimize the user experience through a Design Thinking approach. The method used combines interviews with active users and system log data analysis to gain a comprehensive understanding. The use of system log data complements observation and interview data with actual user behavior data, hopefully resulting in more objective and effective interface redesign recommendations. The results of the study showed that integrating user interviews with system log data was able to identify root causes that were not visible with a qualitative approach alone. The redesign resulted in a simplified transaction flow, repositioning menus based on frequency of use, the addition of a Quick Access feature, balance information on the transaction page, a copy account number feature, increased PIN input responsiveness, and improved application navigation. Test results from the second iteration showed increased transaction completion efficiency, decreased PIN input time, ease of finding key features, and an improved user experience compared to the previous design.